Changing Role of Liver Biopsy Indications in A Tertiary Care Centre: A Histopathological Study - V, Kalaranjini K; Glaxon, Jinu Abraham; Vasudevan, Sheela (Annals of Pathology and Laboratory Medicine, 2019)
Background: The histomorphological study of liver biopsy is the best means to ascertain the nature and signifiÂcance of pathological processes occurring in the liver. The current non-invasive tools are unqualified to replace liver biopsy in clinical practice. Methods: This is a one year prospective study from January 2017 to 2018. A total of twenty five cases suspected to have chronic parenchymal liver disease, inflammatory lesions or neoplastic lesions were included in the study. Detailed history and investigations done including biochemical parameters, radiological and other investigative procedures done were recorded and percutaneous liver biopsy was done using trucut needle. Results: Out of the total 25 liver biopsy done, 60% cases were male, 40% were females. Majority of the patients belonged to the sixth decade (32%). Youngest patient was a 12 year boy with history of intermittent jaundice since birth, and the oldest patient was a 78 year old male. The most prevalent pathological diagnosis was cirrhosis with steatohepatitis with 7 cases (28%), followed by Non Alcoholic Fatty Liver Disease (NAFLD) and autoimmune hepatitis, 12% each. Conclusion: Liver biopsy is the gold standard for diagnosis of chronic liver diseases and plays a valuable role in diagnosis, prognostic and management of liver diseases.